The Effect of Organizational Justice on the Job Performance of Kindergarten Teachers (Damascus University Journal of educational and Psychologyical sciences, 2022)
The study aims to know the effect of organizational justice on the job performance of kindergarten teachers according to the scientific qualification variables, years of experience and training courses. The sample number reached (46) teachers, and to test the hypotheses of the study, a questionnaire consisting of (32) items distributed on three axes was based .The results of the study concluded:There is a statistically significant relationship between organizational justice and job performance of kindergarten teachers in Lattakia.There are statistically significant differences regarding the degree of availability of organizational justice among kindergarten teachers in Lattakia according to the variables of academic qualification and training courses. There are no statistically significant differences in the degree of availability of organizational justice among kindergarten teachers in Lattakia according to the variable of the number of years of experience.   There are statistically significant differences regarding the degree of availability of job performance among kindergarten teachers in Lattakia according to the variables of academic qualification and training courses.   There are statistically significant differences regarding the degree of availability of job performance among kindergarten teachers in Lattakia according to the variable of the number of years of experience.Several suggestions were made based on these results.
Keywords: organizational justice; job performance; female teachers , kindergarten.